A254 IDENTIFICATION OF THE TLR-LIKE RECEPTOR CD180 AND THE ACCESSORY MOLECULE MD-1 DUCK HOMOLOGUES FOR THERAPEUTIC TARGETING IN THE DUCK HEPATITIS B INFECTION MODEL - Yao, Q (J Can Assoc Gastroenterol, 2019)
BACKGROUND: Hepatitis B infection is a leading cause of liver disease with over 240 million chronic carriers. Current protective vaccines elicit protective immune responses in up to 95% of healthy adults but are poorly immunogenic in immunocompromised individuals and there are currently no effective therapeutic vaccines available. CD180, also known as radioprotective 105 kDa protein (RP105), is a Toll-like receptor (TLR), type-1 glycoprotein expressed on antigen presenting cells (APC) in complex with the accessory molecule MD-1. Engagement of antibodies with CD180 promotes proliferation of B cells, and targeting of antigen to CD180 has been shown to enhance antigen-specific B cell and T cell responses. AIMS: The aim of this project is to clone the duck CD180 and MD-1 cDNA and to characterize the expressed protein. METHODS: The duck CD180 (duCD180) and duck MD-1 (duMD-1) cDNAs were obtained by RT-PCR and RACE. The open reading frame of duMD-1 and duCD180 were inserted in eukaryotic expression vectors in frame with distinct carboxy- and amino-terminal purification/detection tags, and expression was verified in 293T cells by immunoblot. RESULTS: The duCD180 cDNA encodes a 660 amino acid (aa) protein that has an aa identity of 52%, 49% and 81% with the respective human, mouse and chicken homologues, whereas the duMD-1 cDNA encodes a 161 aa protein that has an aa identity of 42%, 42% and 84% with human, mouse and chicken MD-1, respectively. Using anti-His6/anti-FLAG antibodies duCD180 and duMD-1 were detected in cell lysates but not culture supernatants of transfected 293T cells. CONCLUSIONS: Our observations suggest significant evolutionary conservation of both CD180 and MD-1 between mammalian and avian homologue proteins. This project will lay the foundation for exploration of CD180-targed immunization studies in the duck hepatitis B infection model. FUNDING AGENCIES: internal funding